IMPLEMENTASI STRATEGI PEMBELAJARAN KONTEKSTUAL DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI SMP NEGERI 2 PINRANG - Henra Ibrahim (IAIN PAREPARE, 2018)
This article discusses the implementation of students' character developmentstrategies in learning Islamic Education in State Yunior High School 2 Pinrang.The purpose of this study is to describe the implementation of contextuallearning strategies in the formation of character of students, to describe theimplementation of contextual learning strategies in character building ofstudents, and to describe the factors related to the strategy of developingcontextual learning strategies to build the character in SMP 2 Pinrang. Thistype of research is descriptive qualitative using the naturalistic paradigm. Theinstruments of this research are: key instrument researchers and usinginterview, observation, and documentation guidelines. Informants interviewedwere principals, vice principals, Islamic Education teachers, and students. Theresults of this study indicate that the implementation of contextual strategieswas carried out through the learning process of Islamic Education by usingmethods in the 2013 curriculum combined with the use of informationtechnology-based learning media. The implementation of the contextual impactstrategy on improving the quality of learning in Islamic Education increases theappreciation of students for religious values, and fosters positive character forstudents. Implementation of contextual strategies by several factors, namely:existing infrastructure and infrastructure, competencies and qualifications ofacademic teachers, active teachers in teacher discussion activities, and theimplementation of the 2013 curriculum related to contextual strategies, literacy,conversation, and the use of information technology-based media.